Simulação tridimensional de reservatórios de petróleo usando modelo Black-Oil com formulação em frações mássicas - Araújo, Josegil Jorge Pereira de (2005)
The present work presents a solution of a two-phase flow (water and oil) for three- dimensional geometries using a simplified black-oil model in terms of mass fractions. The resulting equations were solved by the finite-volume method in conjunction with boundary fitted coordinates and a fully implicit formulation. The interpolation functions UDS (Upstream Differencing Scheme) and CDS (Central Differencing Scheme) with deferred correction were implemented to evaluate the properties in the control volume interfaces. An automatic process for initialization of the variables of the simulator (water saturation, pressure of oil, and capillary pressure) based on an equilibrium condition was also implemented. The simulator was validated using the IMEX, a commercial simulator from CMG (Computer Modelling Group), and cases from the literature using Cartesian and boundary fitted coordinates. The interpolation functions, UDS and deferred CDS, were studied using piston- type and no-piston type flows.